MODEL RAPID APPLICATION DEVELOPMENT (RAD) PADA PENGEMBANGAN APLIKASI PENJADWALAN MATA KULIAH - Arif Amrulloh; Dwi Januarita Ardianing Kusuma; Yudha Saintika; Abednego Dwi Septiadi (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Scheduling courses is a common problem in tertiary institutions, including clashes between lecturers' teaching time, students' rooms, and classes. This study proposes the development of a course scheduling application to overcome lecturers' teaching schedule conflicts, classroom, and student. The course scheduling application developed is website-based, making it easier for users to run the application because it can be accessed using a browser. The application uses PHP programming language and MySQL database as data storage media, while the system development method used is Rapid Application Development (RAD). The RAD method is used because the RAD method emphasizes the development cycle with a short time. The test results using white-box testing show that the developed application is in line with expectations, and no errors were found in all features. The trial results used 265 lecturers' teaching assignment data with the availability of 65 classes, it only took 561 seconds, and no clashes occurred. This scheduling application can process quite a lot of course schedules in a reasonably short time. The results of this study are a website-based course scheduling application that can overcome the problems of lecturer schedule conflicts, student schedule conflicts, teaching time conflicts and lecture room conflicts.